Solution of the Two-Dimensional Stefan Problem by the Singularity-Separating Method (Journal of Computational Mathematics, 1985)
In this paper the idea of "singularity-separating" presented in [10] is used to solve a two-dimensional phase-change problem. A difference scheme with second-order accuracy everywhere, including the region near the boundary between two phases, is constructed for the above problem. Through the computation it is shown that the singularity-separating method, whose accuracy is high, is efficient for two-dimensional phase-change problem.